FTMK Mobile Complaint System - Mohamad Yusuf , Mat Yasit (UTeM, 2009)
The mobile complaint system is a mobile application that allows users from the Faculty of Information and Communication Technology (FTMK) to submit their complaint toward faculty service via the Internet and Java enabled mobile phones. The mobile users have to connect to the server via Internet connection. The administrator web system was created to enable the faculty staffs to manage user submitted complaints. The campus environment was chosen as an application domain of this study because it is highly populated by large numbers of potential test subjects and with strong infrastructure support services. The web application was developed using PHP 5 technologies, while the mobile client was developed using Java ME'S MIDP 2.0. The database for this system was built using MySQL 5.0. Hopefully, this system will contribute lots of benefit in solving some of the challenging problem in mobile computing technologies issues.